2021
DOI: 10.3389/fnagi.2021.716452
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Intra-Species and Inter-Species Prion Conversion and Zoonotic Potential Using Protein Misfolding Cyclic Amplification

Abstract: Prion diseases are fatal neurodegenerative disorders that affect humans and animals, and can also be transmitted from animals to humans. A fundamental event in prion disease pathogenesis is the conversion of normal host prion protein (PrPC) to a disease-associated misfolded form (PrPSc). Whether or not an animal prion disease can infect humans cannot be determined a priori. There is a consensus that classical bovine spongiform encephalopathy (C-type BSE) in cattle transmits to humans, and that classical sheep … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 119 publications
(180 reference statements)
2
10
0
Order By: Relevance
“…Pregnant sheep have been used to study connections between maternal allergies and offspring lung development and risk of allergies [133,134]. Sheep are also considered ideal models for studying neurodegenerative disorders such as Alzheimer's, Parkinson's and Huntington's diseases [135], and due to their susceptibility to scrapie, are widely used to study prion diseases [136,137]. Sheep are also a well-recognized biomedical model for studying immunology [138], vaccine development and safety [139,140], and have been extensively used by our group and others to study the impact of maternal inflammation during pregnancy on offspring development [141].…”
Section: Using An Ovine Model To Study Long-term Outcomes Of Maternal...mentioning
confidence: 99%
“…Pregnant sheep have been used to study connections between maternal allergies and offspring lung development and risk of allergies [133,134]. Sheep are also considered ideal models for studying neurodegenerative disorders such as Alzheimer's, Parkinson's and Huntington's diseases [135], and due to their susceptibility to scrapie, are widely used to study prion diseases [136,137]. Sheep are also a well-recognized biomedical model for studying immunology [138], vaccine development and safety [139,140], and have been extensively used by our group and others to study the impact of maternal inflammation during pregnancy on offspring development [141].…”
Section: Using An Ovine Model To Study Long-term Outcomes Of Maternal...mentioning
confidence: 99%
“…In contrast, the homologous PMCA products (139A-mouse PMCA-PrP res and 263K-hamster PMCA-PrP res ) showed no infectivity against the other animal [23]. Overcoming species barriers of prion infections by PMCA has been repeatedly documented to better understand the transmission between different species of animals and from animal-to-human [24]. Based on PMCA, PrP res can be generated in the reactions of different species of PrP Sc with PrP C from rabbits and dogs that are considered as poorly susceptible and tolerant to prion infection [25,26].…”
Section: Hamster-and Mouse-adapted Scrapie Agents Failed To Induce Co...mentioning
confidence: 99%
“…A further increase in PMCA rounds is warranted. In contrast, high efficiency of PMCA in circumventing species barriers lead to doubt that the species barriers in the real world are potentially underestimated; therefore, careful interpretation of the results of PMCA experiments are required [24]. Nevertheless, numerous species of ruminants have been verified to be susceptible to scrapie infection and bovine spongioform encephalopathy (BSE) [3,[27][28][29].…”
Section: Hamster-and Mouse-adapted Scrapie Agents Failed To Induce Co...mentioning
confidence: 99%
“…PMCA was used to assess the possibility of atypical BSE crossing the species barrier into humans. Neither H- nor L-type BSE induced significant conversion in PMCA in contrast to C-type BSE, indicating that atypical forms of BSE pose a poor zoonotic threat [ 153 , 154 ]. These findings contradict previous results that showed that L-type BSE was able to produce infectivity in a humanized transgenic mouse model overexpressing the human prion protein [ 155 ].…”
Section: Protein Misfolding Cyclic Amplification (Pmca)mentioning
confidence: 99%